An Improved CRISPR/Cas9 System for Genome Editing in Populus by Using Mannopine Synthase (MAS) Promoter - An, Yi; Geng, Ya; Yao, Junguang; Wang, Chun; Du, Juan (Frontiers in Plant Science, 2021)
Gene editing technology has great application prospects for gene function research, breeding improvement, and gene therapy. Application in woody species requires optimization for a higher genome editing efficiency than other plants due to the difficulty during transformation and complexity in polyploidy. In this study, we used poplar 84K (Populus alba × P. glandulosa), which is a model hybrid for studying wood formation and growth, as our testing plant. We developed a new CRISPR/Cas9 system to edit multiple genes simultaneously. Using this system, we successfully knocked out multiple targets of the phytoene desaturase gene 8 in poplar. We found the mutation rate of the new CRISPR/Cas9 System is higher (67.5%) than existing reports in woody trees. We further improved the mutation rate up to 75% at editing sites through the usage of the mannopine synthase (MAS) promoter to drive Cas9. Therefore, the MAS-CRISPR/Cas9 is an improved genome-editing tool for woody plant with a higher efficiency and a higher mutation rate, which may be applied to other plants.